Morphometry of the pelvic ring in definition of biomechanical factors influencing the type of pelvic fracture - Elabjer, Esmat; Nikolić, Vasilije; Matejčić, Aljoša; Kuzmanović Elabjer, Biljana (2009)
Abstract: The aim of the study was to supplement data on pelvic morphology and structural geometry. Using these data, a mathematical and biomechanical model was constructed. The research was divided into two parts. The first part comprised radiogrammetric analysis of pelvic morphology and geometry based on 60 AP x-rays of male and female pelvises. The spatial definition of the pelvis was given by three transverse and one sagittal diameter. Transverse diameters were measured at the level of iliac wings, at the narrowest supraacetabular portion and on the line passing through the center of both femoral heads. The fourth diameter was the height of the pelvis. Geometric properties and structure of pelvic bones and position of muscles in relation to bone elements of the pelvis were analyzed in the second part. Knowing geometric dimensions of the pelvis and the body weight, it is possible to calculate the magnitude of gravitational forces acting upon certain pelvic portions. This biomechanical model serves for simulation of operative methods of fixation and allows search for the optimal solution, which is stable enough to withstand all the forces acting upon fragments of a fractured pelvic ring
Bibliografija: 35 jed
Sažetak
Keywords: Morfometrija -- Zdjelični prsten -- Prijelom zdjelice